THE INHERITANCE OF SOME QUANTITATIVE CHARACTERS OF F2 GENERATION FOR COMMON WHEAT IN SULAIMANI-IRAQ - Rwaida J. A.; T. N. Hama-Amin (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to testing 25 genotypes (5 parents + 10 diallel + 10 reciprocal crosses) using full Diallel mating design in winter season 2021-2022 for F2 generation of common wheat, in two locations. The first was in Qlyasan Agricultural Research Station, College of Agricultural Engineering Sciences; University of Sulaimani located (Lat 35° 34′; N, Long 45° 21′; E, 765 MASL), the second was in Koya Agricultural Station-Ministry of Agricultural (Lat 36° 04′; N, Long 44° 37′; E, 582 MASL). The results of the study confirmed that the mean squares of genotypes was highly significant for all characters in both locations, the same for the mean squares for gca with the exception of grain weight plant-1 in Qlyasan location which was only significant. The mean square for sca was highly significant for most characters at Qlyasan location, while at Koya location it was significant only for grain weight plant-1. The mean square for rca was significant for spike weight plant-1 at Qlyasan location and 1000-grain weight at Koya location and not significant for the other characters. The Diallel cross 1×4 at Qlyasan location and the reciprocal cross 2×1 at Koya location showed the best performance for grain weight plant-1 recording 58.083 and 40.941g plant-1 respectively. The magnitude of σ2sca was more than σ2gca for all characters in both locations indicating the importance of non-additive gene effects in controlling these characters. Heritability in broad sense for Diallel crosses due to grain weight plant-1 was found to be high in both locations, while for reciprocal crosses was low, and it was low for narrow sense for all crosses.